Econometric analysis of crowdfunding campaigns - Papush, Maria; Holý, Vladimír; Veverka, Lukáš; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2023)
Abstract Crowdfunding is one of the most interesting and inspiring topics of recent times and is only getting more popular as time goes by. Studying it allows you to better understand the incentive that arouse public interest, make assumptions about how information is transmitted and wonder as far is possible to predict the behavior of the crowd. Not surprisingly, there are more and more studies exploring the subject. This paper provides a brief overview of articles on the topic of crowdfunding, mainly in terms of the factors that affect the success of the project. In the practical part of the current bachelor thesis, there is a study of the key success factors of the project based on the data of the two most famous reward-based crowdfunding platforms Kickstarter and Indiegogo. The practical part of this thesis is building Lenear Regression and Logistic Regression models using the datasets from the above mentioned platforms. Mentioned models can predict the success of the project to a certain extent.
Vedoucí práce: Vladimír Holý
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2023
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2023
Způsob přístupu: Internet
Keywords: matematické metody v ekonomii [obor bakal. práce]; bakalářské práce; bachelor's theses